(untitled) (Indian Journal of Child Health, 2018)
Background: School absenteeism is prevalent in Madhya Pradesh and other states of India. Various psychosocial, domestic, and health-related factors have been implicated for absenteeism. Objectives: The objectives of this study were to determine the magnitude of school absenteeism and its contributing factors among adolescent students of Ujjain city. Methods: An observational study was conducted in government schools of Ujjain district. Students studying in 6th–8th standard between 11 and 14 years were interviewedusing a predesigned questionnaire. The factors reported for school absenteeism were recorded. Results: A total of 1250 students were studying in the 6th, 7th, and 8th standard. Of these, 434 (34.7%) students had significant absenteeism >2 days/month. Frequent absenteeism (Group A, absenteeism >4 days per month) occurred in 388 (89.4%) and rest were infrequent absentees (Group B, absenteeism ?4 days per month). Analysis of sociodemographic factors revealed significant influence of lower socioeconomic status (A=43.1% and B=28.2%; p=0.03), maternal illiteracy (A=19.3% and B=6.5%; p=0.004), paternal illiteracy (A=12.6% and B=0), rural background (A=23.2% and B=6.5%; p=0.031), and unskilled and semiskilled profession of the father (A=30.9% and B=8.6%; p=0.001) on frequent absenteeism. Helping the mother in the kitchen was the only social factor responsible for the significant absenteeism (A=44.0% and B=26.1%; p=0.02). Watching television (TV) was also reported as a cause of frequent absenteeism. Medical morbidities and school-related factors did not influence significant absenteeism. Conclusion: School absenteeism has a high prevalence in government schools of Ujjain district. Lower socioeconomic status, parental illiteracy, rural background, unskilled occupation, helping the mother in the kitchen, and watching TV resulted in frequent absenteeism.